(untitled) - Enrique Mandado (Englewood Cliffs, New Jersey, 1996)
Key features of this book are: classification and description of PLDs and PLCs, logic controller design methods using PLDs and description of real PLCs, including design examples
Keywords: programmable controllers,programmable logic devices